Use of agronomic conditions, genetics, and processing to improve utilization of sorghum grain - P J Bramel-Cox; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
Sorghum grain is an extremely important crop to both farmers and livestock feeders in the High-Plains states (e.g., from Nebraska to Texas). Kansas leads the nation in sorghum production, and as should be expected, Kansas State University has a long history of research to improve the utilization and marketability of this versatile and hardy crop. This paper is a synopsis of current research at KSU and other universities concerning production and use of sorghum grain for feeding swine. Topics addressed include the relatively small loss in nutritional value (4 to 11 %) as test weight decreases from 55 to 35 lb/bu compared to the extreme discounts experienced by farmers trying to market light grain. Also, an experiment to quantitate yield of utilizable nutrients from com and sorghum was conducted to determine the relative merits of these grain sources when grown with different irrigation and N application strategies. Finally, sorghum parent lines have been identified with improved digestibility, and alternative milling procedures (e.g., fine-grinding and extrusion) have been identified that should greatly improve the competitiveness of sorghum grain as a feedstuff of choice for swine diets.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Sorghum grain; Irrigation; N application; Genotype; Process; GF; Starter